The elastic modulus of isolated polytetrafluoroethylene filaments - Patrick Drawe; Nils Lüttschwager; Martin Suhm (ScienceOpen Research, 2014)
We report vibrational Raman spectra of small extended perfluoro-n-alkanes (CnF{2n+2} with n=6, 8-10, 12-14) isolated in supersonic jet expansions and use wavenumbers of longitudinal acoustic vibrations to extrapolate the elastic modulus of cold, isolated polytetrafluoroethylene filaments. The derived value E = 209(10) GPa defines an upper limit for the elastic modulus of the perfectly crystalline, non-interacting polymer at low temperatures and serves as a benchmark for quantum chemical predictions.